An investigation into mechanical wound parameters that may affect the extent of internal decay in wounded stems of big-leaved acacia (Acacia mangium Willd.) and ear-leaved acacia (Acacia auriculiformis A. Cunn. ex Benth.). Issue 4 (1st October 2020) - Lap, Yiu Chun; Slater, Duncan
ABSTRACT: Mechanical injuries to trees can cause an early onset of decay and subsequent early removal of trees. This study assessed six factors that might affect the extent of internal decay in mechanically wounded stems of big-leaved acacia ( Acacia mangium Willd.) and ear-leaved acacia ( Acacia auriculiformis A. Cunn. ex Benth.). The extent of internal decay was determined by using a Resistograph® microdrill on 71 standing specimens of A. mangium and A. auriculiformis in Tai Po Industrial Estate, Hong Kong. The ratio of sound wood to the diameter of each stem was calculated by drilling perpendicular to each stem wound's surface at three locations. The wound's depth was a significant factor in predicting the extent of internal stem decay, with greater depth of wounding relating to a greater extent of internal decay, predicting approximately 30% of the variation. The factor of stem wound area was not significantly associated with the severity of the internal decay in A. auriculiformis, which, from this analysis, exhibited more decay resistance than A. magnium . It is concluded that through quantitative research into decay in standing trees a new model for the progress of wood decay could be developed by using a region-growing approach.